Psychology of nerve injury, repair, and recovery: a systematic review - Adu, Yaw; Cox, Cameron T.; Hernandez, Evan J.; Zhu, Christina; Trevino, Zachary; MacKay, Brendan J. (Frontiers in Rehabilitation Sciences, 2024)
BackgroundPeripheral nerve injuries (PNIs) are associated with significant physical and psychological challenges, impacting both functional recovery and quality of life. Despite the physical focus of traditional treatments, psychological factors play a crucial role in the outcomes of PNI repair and recovery.ObjectivesThis systematic review aims to evaluate the impact of psychological and social factors on the repair and recovery of peripheral nerve injuries.MethodsA comprehensive literature search was conducted in PubMed/Medline, EMBASE, and Cochrane databases, covering studies from January 1985 to December 2022. A total of 36,190 records were identified, and after screening with Rayyan AI and applying inclusion criteria, 111 articles were selected for review.ResultsThe review highlights that pre-existing psychological conditions, as well as psychological responses to the injury and treatment, significantly influence recovery outcomes in PNI patients. Psychological interventions, when integrated into standard care, may improve functional recovery and quality of life.ConclusionsPsychosocial factors are critical in the management of PNIs and should be incorporated into treatment algorithms to enhance patient outcomes. Future research should focus on developing and integrating psychological support strategies in PNI treatment protocols.